How much Artistic Freedom is permitted when it comes to Language? - Analysis of a Crime Novel - Svoboda, Manuela; Petra Zagar-Sostaric (European Journal of Social Science Education and Research, 2020)
In this article a closer look will be taken at the issue of inaccurately using a foreign language, i.e. German in this particular case, in a crime novel or thriller. Of course, in fiction the author has complete artistic freedom to invent and present things as he/she intends and it doesn`t necessarily have to be realistic or legitimate. But what happens when it comes to an existing language being quoted in fiction? For this purpose David Thomas’ thriller “Blood Relative – How well do you know the one you love?” is analysed regarding parts in which German quotes are used. As the plot is located partly in England and partly in former East Germany (GDR) and the protagonist’s wife is of German origin, direct speech, titles and names are used in German. Subsequently, they are translated into English by the author in order to be understood by the English reader. However, there are many grammar, spelling and semantic mistakes in these German expressions and common small talk quotes. This begs the question, is it justified to disregard linguistic correctness with regards to artistic freedom given the fact that we are dealing with a fictional thriller, or is it nevertheless necessary to be precise concerning foreign language usage? How far may one “test” their artistic freedom in this particular case? In order to answer these questions a detailed analysis of the thriller is performed, concerning artistic freedom and modern literature/light fiction as well as the German language used in quotes and direct speech.